Small-sided games (ssg) internal and external load on different pitch sizes in young elite women football players - Chatzicharistou, P.; Semaltianou, E.; Lola, A.; Stavropoulou, G.; Trigonis, I. (Journal of Human Sport & Exercise, 2025)
The present study aimed to assess and compare the internal and external training loads experienced by elite young female football players during small-sided games (SSGs) conducted on two different pitch sizes. Eight athletes (age: 19.6 ± 3.7 years) from a top-tier Greek women`s football team participated in two training sessions and one official match. GPS tracking and heart rate monitoring were used to collect data on total distance, speed zones, sprint count, maximum speed, and heart rate distribution across five intensity zones. Two SSG formats (4v4) were implemented: one on a 20×30m pitch (75m²/player) and one on a 30×40m pitch (150m²/player), each consisting of four 4-minute bouts with 2-minute passive recovery. The results revealed no significant differences in internal load (heart rate responses) between the two pitch sizes. However, external load metrics varied notably: the smaller pitch induced more frequent accelerations and decelerations (p < .05), while the larger pitch resulted in longer total distances and more sprints (p < .05). These findings highlight the influence of pitch size on movement demands, with smaller areas favouring anaerobic, change-of-direction actions and larger areas promoting mostly aerobic and high-speed activities. The study emphasizes the effectiveness of SSGs in conditioning programs and supports their role in developing both aerobic and anaerobic fitness within realistic game contexts. The application of GPS technology enabled precise workload quantification, offering valuable insights for individualized training design. Importantly, this research addresses a gap in the literature regarding elite young women footballers, providing practical guidance for coaches aiming to optimize performance and minimize injury risk through targeted SSG configurations.